Adherence to acute otitis media diagnosis and treatment guidelines among Israeli otolaryngologists. (April 2017) - Marom, Tal; Bobrow, Mathan; Eviatar, Ephraim; Oron, Yahav; Ovnat Tamir, Sharon
Abstract: Introduction: The recent Israeli acute otitis media (AOM) guidelines, drafted mainly by pediatricians and family physicians in 2013, addressed diagnostic and therapeutic issues, in order to reduce over-diagnosis and treatment. These guidelines are considered as the 'standard of care' for AOM management. While the adherence rate of pediatricians to previous Israeli AOM guidelines (2004) was reported to be high (>85%), the compliance of otolaryngologists has not been studied. Methods: An anonymous 19-item questionnaire was circulated among practicing Israeli otolaryngologists (residents [n = 93], specialists [n = 283]). All the items were scored according to the number of correct answers in line with the guidelines, and summed on a 0–100 scale. Results: Response rate was 34% (n = 127). Overall, scores of correct answers of residents (n = 48, 52% of all residents) and specialists (n = 79, 28% of all specialists) were similar, and showed comparable moderate adherence to both guidelines: 55.7 vs 58.3 (p = 0.26). Residents were more likely to adhere to the U.S. guidelines, when compared to specialists (score difference 6.1 vs 2.8, p = 0.008). Responders preferred the microscope for diagnosis (48%), over the recommended (pneumatic) otoscope (62%) (p = 0.05), and were more likely to start antibiotic therapy (62%), rather than the 'watchful waiting' (38%) (p = 0.03). Concerning antibiotic treatment, 50% of otolaryngologists prescribed amoxicillin as recommended, at 60–80 mg/kg/d. Conclusion: The moderate adherence rate suggests that the guidelines were partially adopted by otolaryngologists, who use different instrumentation than recommended, and treat more severe/complicated cases. Over-treatment with antibiotics and inaccurate dosing regimens are still common. Better implementation of the AOM guidelines among otolaryngologists should be performed in designated training platforms.